Critical Success Factors Affecting E-Government Policy Implementation in Pakistan - Waqar Siddique (JeDEM - eJournal of eDemocracy & Open Government, 2016)
Abstract: This research turns e-government policy into practice in two ways, firstly to distil the lessons from existing evidence and experience about e-government implementation of policies and secondly by assessing the quality of the evidence, gaps in the existing research, and ways that research findings can support the implementation process in Pakistan. The main question, therefore, is how far national policy aspirations translate into actions, which are meaningful, tangible and measurable at a local level. This means the consistency of the goals at all levels remain the same i.e., macro and micro levels. This study identifies critical factors that determine the faith of policy implementation in Pakistan. The proposed model, which is based on these critical factors, is validate by analyzing different hypothesizes using empirical analysis i.e., quantitative and qualitative. This study provides a fair idea about intrinsic and extrinsic behavior of these critical success factors towards e-government policy implementation concerning Pakistan. This study also facilities successful e-government implementation in Pakistan by setting direction and guidelines for all implementation stakeholders.